Plan de mejora en el área comercial de la Empresa AR Ingeniería & Equipos. (2023)
The following work discloses the formulation of an improvement plan that contributes to greater profitability in the rental of equipment for work at height of the company AR Ingeniería y Equipos. It is divided into III phases that allowed an organization and development of the information properly, thanks to the tools used, a strategy can be established in the improvement plan. The phases will be described below: I Phase: Conceptualization of the investigation II Phase: Conceptual approach III Phase: Remains of the specific objectives.